If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 12 + -13 Combine like terms: 12 + -13 = -1 x = -1 Solving x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = -1
| x+4=5+y | | 2a^2=6-4a | | -51+10x=6x+57 | | 2x^2+6-20=3x+1 | | abs(3x+1)-9=-4 | | 8+2(7v-2)=-2(4v-3)+8v | | 15+15+15+15+15+15+15+15= | | -3x-43=20-6x | | 8y-9+2(4y+3)=-2(y+9) | | 8x^2-72x=-144 | | 7x-9=3(X+3) | | 4(w-6)-6=-5(-4w+9)-6w | | 4=6+2w | | 4x+28=10x | | 18x-36=48x | | -7x+8=3x-40 | | 2(u-3)-6=-2(-2u+7)-8u | | -2(u+2)=4(4u-1)+4u | | 6x^2-4x-112=0 | | -104-4x=58-10x | | -11(y+3)+4(4y-6)=4(y-3)+11 | | G+4200=580 | | .5x^2-3x+4.5=0 | | 7(5+3x)-6(x+5)=0 | | 8x+4-2(-7x-3)=4(x-1) | | 42x=80+30x | | -59+7x=31+2x | | Y-658=2532 | | 2=1+x-16 | | X+65=35 | | y^2-y+201.25=0 | | -10x=5x-45 |